Analisis Kinerja Pajak Daerah Tulungagung - Dwi Anggoro, Damas; Muttaqin, Andhyka (Jurnal Ilmiah Administrasi Publik, 2019)
Good local tax management is a strategy in optimizing local tax revenues. This can increaseÂ  Local Own-source Reveneu (PAD), which is a benchmark for regional independence and can provide prosperity to the community through regional development. Analysis of local tax performance is important to determine the condition of the problems that occur at this time regarding the management of local taxes in Tulungagung district. There are four technical analyzes used, namely the analysis of growth, contribution, performance and overlay analysis which is a tool to dissect all objects of regional tax in Tulungagung district. Thus a strategy can be formulated that can provide concrete recommendations to optimize local tax revenues as one of the spearheads in increasing PAD and prosperity in Tulungagung District.